Financing Innovation: A Complex Nexus of Risk & Reward - Sourish Dutta (SSRN, 2015)
The crucial and growing role performed by different financial intermediaries such as venture capitalists and angel investors as well as more traditional intermediaries such as commercial banks in developing entrepreneurial or innovative firms and boosting product market innovations has led to great research interest in the economics of innovation and entrepreneurial finance. Besides this, there are some important factors or developments which have affected the entrepreneurial finance in general as well as its influence upon different entrepreneurial or innovative firms. Indeed, it is also true that the financial and ownership structures of the different entrepreneurial firms and the legal as well as institutional environment, in which they operate, itself affects the product market innovations (Chemmanur and Fulghieri, 2014). Therefore, in this paper I want to target a broad theme i.e. analysis of the mechanisms behind this scenario, especially, in the context of Indian market system.
Keywords: G11; G24; O31; O32; 330; Innovation; Financing Frictions; Entrepreneurial Finance